PENGARUH LINGKUNGAN DAN HARGA “KANTY STORE TALIWANG” DI SUMAWA TERHADAP MINAT KONSUMEN DALAM MELAKUKAN PEMBELIAN - Melia, Lala Andra; Hilmiati, Hilmiati; Retnowati, Weni (Jurnal Magister Manajemen, 2023)
The purpose of this study is to ascertain the relationship between store ambiance and consumers’ desire to return to Taliwang Kanty stores as well as the relationship between price and that intention. The inhabitants of Sumbawa who have made purchases at the Taliwang Kanty Store make up the study’s demographic. A survey research methodology is used in the data collection process. Online surveys and questionnaires are used in data gathering strategies together with questionnaires as the data collecting tool. The data were processed used SPSS 26.0 for Windows by conducting validity tests, reliability tests, classic assumption tests, normality tests, multicollinearity tests, multiple linear regression tests, t-tests, and coefficient of determination tests. The results of this study show that store atmosphere (X1) has an effect on repurchase intention with a t-count of 3.591 ˃ 1.984 with a significance value of 0.001 which is below the required significant value of 0.05. Price (X2) has an effect on repurchase intention with a t-count value of 6.713 ˃ 1.984 with a significance value of 0.000 because it is below the implied significant value of 0.05. According to the results of this study, it is suggested to the owner of the Taliwang Kanty Store to further improve the store atmosphere and pay more attention to current trends and future trends and continue to provide products with the latest trends that many consumers choose in determined fashion.